Investigation of three clusters of COVID-19 in Singapore: implications for surveillance and response measures. Issue 10229 (28th March 2020) - Pung, Rachael; Chiew, Calvin J; Young, Barnaby E; Chin, Sarah; Chen, Mark I-C; Clapham, Hannah E; Cook, Alex R; Maurer-Stroh, Sebastian; Toh, Matthias P H S; Poh, Cuiqin; Low, Mabel; Lum, Joshua; et al.
Summary: Background: Three clusters of coronavirus disease 2019 (COVID-19) linked to a tour group from China, a company conference, and a church were identified in Singapore in February, 2020. Methods: We gathered epidemiological and clinical data from individuals with confirmed COVID-19, via interviews and inpatient medical records, and we did field investigations to assess interactions and possible modes of transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Open source reports were obtained for overseas cases. We reported the median (IQR) incubation period of SARS-CoV-2. Findings: As of Feb 15, 2020, 36 cases of COVID-19 were linked epidemiologically to the first three clusters of circumscribed local transmission in Singapore. 425 close contacts were quarantined. Direct or prolonged close contact was reported among affected individuals, although indirect transmission (eg, via fomites and shared food) could not be excluded. The median incubation period of SARS-CoV-2 was 4 days (IQR 3–6). The serial interval between transmission pairs ranged between 3 days and 8 days. Interpretation: SARS-CoV-2 is transmissible in community settings, and local clusters of COVID-19 are expected in countries with high travel volume from China before the lockdown of Wuhan and institution of travel restrictions. Enhanced surveillance and contact tracing is essential to minimise the risk of widespread transmission in the community. Funding: None.